Щодо адміністративного оскарження порушень прав споживачів суб’єктом господарювання у сфері розподілу природного газу - Юшкевич, О. Г.; Iushkevych, O. G.; ORCID: http://orcid.org/0000-0003-0024-6070 (Форум права. – 2018. – № 5 (53). – С. 80-91, 2018)
Висвітлено особливості адміністративного оскарження порушень прав споживачів суб’єктами господарювання у сфері розподілу природного газу, які займають домінуюче становище на ринку та є природною монополією (Публічні акціонерні товариства "Львівгаз", "Київгаз", "Харківгаз"). Здійснено загальний огляд законодавчих та теоретичних засад функціонування інституту адміністративного оскарження в Україні. Проаналізовано правове регулювання діяльності суб'єктів господарювання, які займають домінуюче становище на ринку газу. Зроблено висновок про наявність законодавчої бази та чітких механізмів захисту прав споживачів газу від порушень з боку суб’єктів господарювання у сфері розподілу природного газу. З'ясовано типові порушення у діяльності суб’єкта господарювання у сфері розподілу природного газу. Розглянуто інструменти адміністративного оскарження у сфері розподілу природного газу та їх ефективність.

The author has highlighted specific features of administrative appeal of the violations of consumer rights by a business entity in the field of natural gas distribution, which occupies a dominant position on the market and is a natural monopoly (Public joint-stock company "Lvivhaz", "Kuivhaz", "Kharkivhaz"). It has been established that the main advantages of administrative appeal as a legal pre-trial method of protection and restoration of the rights of gas consumers in the field of natural gas market’s functioning are economical efficiency, operational efficiency, less formalism and the opportunity to review the decision, action or omission of the business entity in the field of natural gas distribution for their expediency. A general overview of legislative and theoretical principles of the functioning of the institution of administrative appeal in Ukraine has been carried out. It has been established that nowadays the legislative definition of the term “administrative appeal” and the unified for all public authorities term of the consideration of citizens’ appeals do not exist; however, the content, procedure, terms of filing and reviewing complaints within the appeals of citizens and litigation are rather clearly delimited; the subjects authorized to consider complaints filed within administrative appeal procedure and a list of decisions, actions (omission) of public authorities that may be appealed are regulated. The legal regulation of the activity of business entities that occupy a dominant position in the gas market has been analyzed. It has been concluded that there is a legislative base and clear mechanisms for protecting the rights of gas consumers from the violations by the business entity in the field of natural gas distribution. The author has clarified the typical violations within the activities of the business entity in the field of natural gas distribution, in particular, the absence of a schedule for checking the indicators of gas meter by the employees of the business entity in the field of natural gas distribution, the absence of any documents based on the results of the control over the site of the accounting, violation of the deadlines of conducting inspections of gas meter by the employees of the business entity in the field of natural gas distribution, extortion by the employees of the business entity in the field of natural gas distribution for periodic verification, maintenance and repair of gas meter, etc. The tools of administrative appeal in the field of natural gas distribution and their efficiency have been studied. Thus, effective means of appealing decisions, action or omission of the business entity in the field of natural gas distribution are applications to the National Commission that carries out state regulation in the spheres of energy and utilities and to the Government “hotline”, in contrast to applications to the management of the business entity in the field of natural gas distribution.

Освещены особенности административного обжалования нарушений прав потребителей субъектами хозяйствования в сфере распределения природного газа, которые занимают доминирующее положение на рынке и является естественной монополией (Публичные акционерные общества "Львовгаз", "Киевгаз", "Харьковгаз"). Осуществлено всеобщее обозрение законодательных и теоретических основ функционирования института административного обжалования в Украине. Проанализировано правовое регулирование деятельности субъектов хозяйствования, занимающих доминирующее положение на рынке газа. Сделан вывод о наличии законодательной базы и четких механизмов защиты прав потребителей газа от нарушений со стороны субъектов хозяйствования в сфере распределения природного газа. Выяснены типичные нарушения в деятельности предприятия в сфере распределения природного газа. Рассмотрены инструменты административного обжалования в сфере распределения природного газа и их эффективность.
In regard to administrative appeal of the violation of the rights of consumers by a business entity in the field of natural gas distribution
Юшкевич, О. Г. Щодо адміністративного оскарження порушень прав споживачів суб’єктом господарювання у сфері розподілу природного газу [Електронний ресурс] / О. Г. Юшкевич // Форум права. – 2018. – № 5 (53). – С. 80-91. – Режим доступу: http://forumprava.pp.ua/files/080-091-2018-5-FP-Iushkevych_11.pdf.
Юшкевич, О. Г. (2018). Щодо адміністративного оскарження порушень прав споживачів суб’єктом господарювання у сфері розподілу природного газу. Форум Права, 53(5). 80–91. DOI: http://doi.org/10.5281/zenodo.2550448.
Keywords: ринок природного газу; Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; скарга; адміністративне оскарження; захист прав споживачів; споживачі природного газу; суб'єкти господарювання; complaint; administrative appeal; protection of the rights of natural gas consumers; business entities; natural gas market; жалоба; административное обжалование; защита прав потребителей; потребители природного газа; субъекты хозяйствования; рынок природного газа